2016
DOI: 10.4314/jasem.v20i1.11
|View full text |Cite
|
Sign up to set email alerts
|

Hematobiochemical changes of lead Poisoning and amelioration with Coconut (<i>Cocos nucifera</i> L.) Water in wistar albino rats

Abstract: ABSTRACT:To determine the ameliorative effect of coconut water on haematobiochemical changes due to lead poisoning in wistar albino rats for six weeks, sixty rats were assigned to four groups. 0.10g/l of lead and 75ml coconut (cocus nucifera l.) water were given orally for six weeks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 19 publications
(24 reference statements)
0
3
1
Order By: Relevance
“…There was a significant decrease in hematological parameters like TEC, Hb, and PCV in lead treated rats, where as TLC values were increased compared to control group. These findings were in agreement with [8,11] . Hematological changes might be attributed to the toxic effect of lead on cell metabolism, interaction with calcium as secondary mediator and inhibition of enzymatic activities such as aminolevulinic acid dehydratase which play key role of heme biosynthesis and other erythrocyte enzymes [3] .…”
Section: Resultssupporting
confidence: 93%
“…There was a significant decrease in hematological parameters like TEC, Hb, and PCV in lead treated rats, where as TLC values were increased compared to control group. These findings were in agreement with [8,11] . Hematological changes might be attributed to the toxic effect of lead on cell metabolism, interaction with calcium as secondary mediator and inhibition of enzymatic activities such as aminolevulinic acid dehydratase which play key role of heme biosynthesis and other erythrocyte enzymes [3] .…”
Section: Resultssupporting
confidence: 93%
“…Platelet level was decreased in rats treated with C. papaya leaves [52]. This finding however contrasts a research conducted by Enagbonma et al [48] who reported that following the administration of 0.10mg/kg of lead to albino rats, the platelet levels reduced when compared to the control. Sule et al [51], reported that the levels of lymphocytes increased in rats pretreated with Carica papaya when compared with rats administered with CCl4 only.…”
Section: Discussioncontrasting
confidence: 61%
“…Jassim and Hassan [47], also reported that lead acetate when given orally to female rats at a dose of 10 mg/kg produced significant increase in percentage of WBC count and MCV. In contrast, a research conducted by Enagbonma et al [48] revealed that when 0.10mg/kg of lead was administered to albino rats, the RBC levels reduced when compared to the control. This could be due to the difference in dosage of lead administered.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…11 Tender coconut water to prevent oxidative stress, reduce free radicals, increase Antioxidant Enzym, decrease lipid peroxidative. 7,11,[22][23][24] The result of this study indicate that tender coconut water at a dose of 8 mL/200 gBW is significantly increased hemoglobin, hematocrit and erythrocyte levels in male wistar strain rats induced by Pb, these results are linear with previous research by Jesuorsemwen et al that the mean hematocrit and erythrocyte levels increased in the administration of tender coconut water, 25 the results of other research conducted by Safitri et al stated that the administration of tender coconut water can increase the mean of blood hemoglobin level. 26 Fa'iza et al stated that there were differences in blood Hemoglobin level before and after consumption of green coconut water in workers exposed to lead (Pb) with p value = 0.001.…”
Section: Discussionmentioning
confidence: 99%